The Influence of Monoamine Oxidase Variants on the Risk of Betel Quid-Associated Oral and Pharyngeal Cancer - Ping-Ho Chen; Bin Huang; Tien-Yu Shieh; Yan-Hsiung Wang; Yuk-Kwan Chen; Ju-Hui Wu; Jhen-Hao Huang; Chun-Chia Chen; Ka-Wo Lee (The Scientific World Journal)
Betel quid (BQ) and areca nut (AN) (major BQ ingredient) are group I human carcinogens illustrated by International Agency for Research on Cancer and are closely associated with an elevated risk of oral potentially malignant disorders (OPMDs) and cancers of the oral cavity and pharynx. The primary alkaloid of AN, arecoline, can be metabolized via the monoamine oxidase (MAO) gene by inducing reactive oxygen species (ROS). The aim of this study was to investigate whether the variants of the susceptible candidate MAO genes are associated with OPMDs and oral and pharyngeal cancer. A significant trend of MAO-A mRNA expression was found in in vitro studies. Using paired human tissues, we confirmed the significantly decreased expression of MAO-A and MAO-B in cancerous tissues when compared with adjacent noncancerous tissues. Moreover, we determined that MAO-A single nucleotide polymorphism variants are significantly linked with oral and pharyngeal cancer patients in comparison to OPMDs patients [rs5953210 risk G-allele, odds ratio = 1.76; 95% confidence interval = 1.02-3.01]. In conclusion, we suggested that susceptible MAO family variants associated with oral and pharyngeal cancer may be implicated in the modulation of MAO gene activity associated with ROS.